Effects of Different Blood Flow Meters and Diets on Volatile Fatty Acids and Other Metabolites into Portal Blood of Sheep - Bugi Rustamadji (Faculty of Animal Science, Universitas Gadjah Mada, 1997)
Artikel dalam bentuk PDF